Analisis Implementasi dan Tantangan Kurikulum Merdeka bagi Guru di SDN 101766 Bandar Setia (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The Merdeka Curriculum provides flexibility for schools to design more innovative and independent learning. However, its implementation faces challenges such as limited facilities, teacher readiness, and policy disparities. This study analyzes these challenges using a literature review method. The results indicate that the success of the Merdeka Curriculum depends on teacher training, technological support, and collaboration between schools, parents, and the government.